Processor performance metrics analysis and implementation for MIPS using an open source OS - Varuna Eswer; Sanket Dessai (Institute of Advanced Engineering and Science, 2021)
Processor efficiency is a important in embedded system. The efficiency of the processor depends on the L1 cache and translation lookaside buffer (TLB). It is required to understand the L1 cache and TLB performances during varied load for the execution on the processor and hence studies the performance of the varying load and its performance with caches with MIPS and operating system (OS) are studied in this paper. The proposed methods of implementation in the paper considers the counting of the instruction execution for respective cache and TLB management and the events are measured using a dedicated counters in software. The software counters are used as there are limitation to hardware counters in the MIPS32. Twentyseven metrics are considered for analysis and proper identification and implemented for the performance measurement of L1 cache and TLB on the MIPS32 processor. The generated data helps in future research in compiler tuning, memory management design for OS, analyzing architectural issues, system benchmarking, scalability, address space analysis, studies of bus communication among processor and its workload sharing characterization and kernel profiling.